Kānphatthanā thī yangȳưn = Sustainable development - Phra Thēpwēthī (Prayut) (Samnakphim Mūnnithi Kōmonkhīmth̨ōng : Khlet Thai čhatčhamnāi, 1997)
Study on sustainable development with reference to Thailand.